Tumor microenvironment conditions that favor vessel co-option in colorectal cancer liver metastases: A theoretical model. (June 2021) - Rada, Miran; Lazaris, Anthoula; Kapelanski-Lamoureux, Audrey; Mayer, Thomas Z.; Metrakos, Peter
Abstract: Vessel co-option is an alternative strategy by which tumour cells vascularize and gain access to nutrients to support tumour growth, survival and metastasis. In vessel co-option, the cancer cells move towards the pre-existing vasculature and hijack them. Vessel co-option is adopted by a wide range of human tumours including colorectal cancer liver metastases (CRCLM) and is responsible for the effectiveness of treatment in CRCLM. Furthermore, vessel co-option is an intrinsic feature and an acquired mechanism of resistance to anti-angiogenic treatment. In this review, we describe the microenvironment, the molecular players, discovered thus far of co-opting CRCLM lesions and propose a theoretical model. We also highlight key unanswered questions that are critical to improving our understanding of CRCLM vessel co-option and for the development of effective approaches for the treatment of co-opting tumours.